Analysis of Verbal Harassment on Women in The Comments Column of The Tiktok Account @Kinderflix.Idn - Gusti Faradiazhary, Sahnaz; Muhammad Fadeli; Delmarrich Bilga Ayu Permatasari (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
Women are often subjected to verbal abuse in real life, as well as in digital life. Verbal harassment of women does not develop solely on certain women, but it does not rule out the possibility for any woman to get verbal harassment. Anisa Rostiana, a toddler education content host on TikTok @Kinderflix.idn, has received negative comments with various kinds of verbal abuse. Sadly, most verbal abuse comes from 'anonymous' accounts deliberately created by irresponsible people in cyberspace to comment at will. This research proves the verbal abuse Anisa received in the @Kinderflix.idn comment section. This verbal abuse was analyzed using Philipp Mayring's Content Analysis theory. Verbal harassment is divided into three categories; the first is Verbal Sexual Harassment, which contains comments leading to sexual activities to fulfill men's fantasies. Second, Euphemism Verbal Harassment by utilizing words/sentences that have been softened to have a double or ambiguous meaning. The last is the objectification of women, which is very thick, by making Anisa an object/good that can be watched, contested, and claimed as property by others.